Conceptual framework : the determinant factors of intention to use interactive kiosk technology in the museum / Mohd Nasiruddin Abdul Aziz ... [et al.] - Abdul Aziz, Mohd Nasiruddin; Harun, Siti Norlizaiha; S Mahadi, Sharifah Raudzah; Johari, Mohd Hisham; Abdullah, Muhammad (2021)
Interactive kiosk technology (IKT) has become one of the most popular learning tools in the museum sectors because of the effectiveness to increase the level of experience and cognitive engagement among the visitors. However, not all the visitors are interested to use the IKT provided caused by several factors that have been revealed by the previous studies. Based on the content analysis from an extensive literature review of Technology Acceptance Model (TAM) studies, this paper proposes a conceptual framework with highlighting the relationship between the belief factors (perceived usefulness, perceived ease of use) and design factors (system support, user interface design, navigation, accessibility, and comfortability) towards the intention to use the IKT in the museum. Theoretically, this paper contributes to the new perspective and understanding of the technology adoption study in the museum setting for further research.